Mapping Netizen Responses on Kompas.com Regarding Nickel Mining in Raja Ampat - Dhia Khinanti Audi Priyono; Moch. Fuad Nasvian (Journal of Social Research, 2025)
Mining schemes are often promised to bring prosperity and progress, but on the other hand, mining activities that encroach on most of Indonesia's landscape cause environmental pollution, ecological degradation, and social crises that worsen Indonesia's condition. This study analyzes public responses to nickel mining in Raja Ampat through netizen comments on the Kompas.com YouTube platform. This research uses exploratory computational content analysis (CATA) with Voyant tools. The data comes from comments on 58 Kompas.com YouTube videos with titles related to "Raja Ampat Nickel Mining." Data scraping was performed using JavaScript on June 28 2025, yielding 8,422 comments. This study presents netizen discussions through Word Cloud, Corpus Collocates, co-occurrence, and KWIC analysis. The results of the study reveal that the most frequently appearing corpus in this issue is about environmental damage and its impact on local communities. Through computational content analysis, words such as "nature," "people," and "destroy" describe netizens' concerns about the consequences of nickel mining in ecologically valuable areas such as Raja Ampat. Future researchers may consider several things, such as expanding the data collected from other social media platforms to enrich the data and understanding of public opinion on this issue in the digital space. Subsequent researchers could also conduct qualitative research, such as interviews. with relevant parties, to provide in-depth information on mining issues. Future research could focus on similar issues in other regions facing problems related to mining and sustainability.